Dynamic serum lactate dehydrogenase monitoring during the acute phase and association with in-hospital all-cause mortality risk in large vessel occlusion acute ischemic stroke patients - Weiwei Gao; Lijuan Cai; Xingyu Chen; Renjing Zhu (European Journal of Medical Research)
Abstract Background Lactate dehydrogenase (LDH), a key glycolytic enzyme released abundantly during cellular injury, has been established as a prognostic biomarker in ischemic stroke. However, the dynamic changes and predictive value of serum LDH during the acute phase in patients with large vessel occlusion acute ischemic stroke (LVO-AIS) remain insufficiently characterized. Methods This retrospective cohort study consecutively enrolled 414 LVO-AIS patients who underwent endovascular treatment (EVT) at a comprehensive stroke center between January 2019 and November 2024. Serum LDH levels were measured at admission, on post-EVT day 1, and day 3. In-hospital all-cause mortality (IHM) served as the primary endpoint. Friedman tests assessed longitudinal trends in LDH levels, with Durbin–Conover post hoc pairwise comparisons. Progressively adjusted multivariable logistic regression models evaluated associations between LDH and IHM. Restricted cubic spline (RCS) regression explored potential non-linear relationships, while subgroup analyses and interaction testing assessed the consistency and robustness of associations. Results Among 414 patients, 58 (14.0%) experienced IHM. Baseline LDH levels showed no significant difference between survivors and non-survivors (P = 0.108), whereas the non-survivor group demonstrated significantly elevated LDH levels on post-EVT days 1 and 3 (P < 0.001). In the fully adjusted model, each 10 U/L increase in day-3 LDH was associated with a 7% increased mortality risk (P < 0.001). The highest LDH quartile conferred a 10.75-fold increased mortality risk compared with the lowest quartile (P = 0.002). ROC analysis revealed good predictive performance for day-3 LDH levels (AUC = 0.74) and absolute change from baseline to day 3 (ΔLDH, AUC = 0.74). RCS analysis confirmed a significant linear dose–response relationship between LDH and IHM (both P-nonlinear > 0.05). No significant interaction effects were observed across subgroups (all P for interaction > 0.05). Conclusions Dynamic LDH monitoring, particularly day-3 post-EVT levels, provides valuable prognostic information for risk stratification in LVO-AIS patients. The temporal LDH pattern may reflect the evolution of cerebral tissue injury and reperfusion injury, facilitating early identification of high-risk patients requiring intensified monitoring and potential therapeutic interventions.